PERANCANGAN WEB PERPUSTAKAAN PADA SMP TARUNA BHAKTI DEPOK - Maryono, Yoyok; Darwati, Ida (LPPM Universitas Nusa Mandiri, 2017)
The school library is a place that provides textbooks and readings for students and teachers to support the teaching and learning process. The system of borrowing and returning books in libraries still using the manual system is feared that there will be mistakes when recording book lending, the number of books available, the difficulties in finding books and what information books are available. Implementation of web-based libraries is expected to facilitate students / teachers easy to find out what books are available, librarians become more helpful in monitoring the stock of books and the process of borrowing and return of books, so as to be able to solve the problems that are feared occurred.